Person-centred eHealth intervention for patients on sick leave due to common mental disorders: study protocol of a randomised controlled trial and process evaluation (PROMISE) - Ingibjörg H Jonsdottir; Hanna Gyllensten; Lilas Ali; Andreas Fors; Karl Swedberg; Inger Ekman; Matilda Cederberg; Kristina Glise (BMJ Open)
Introduction The number of people dealing with common mental disorders (CMDs) is a major concern in many countries, including Sweden. Sickness absence resulting from CMDs is often long-lasting and advancing return to work is a complex process impacted by several factors, among which self-efficacy appears to be an important personal resource. Person-centred care (PCC) has previously shown positive effects on self-efficacy however this needs to be further investigated in relation to patients with CMDs and in an eHealth context.Methods and analysis This study is an open randomised controlled trial comparing a control group receiving standard care with an intervention group receiving standard care plus PCC by telephone and a digital platform. The primary outcome measure is a composite score of changes in sick leave and self-efficacy. Participants will include 220 primary care patients on sick leave due to CMDs and data will mainly be collected through questionnaires at baseline and 3, 6, 12 and 24 months from the inclusion date. Inclusion is ongoing and expected to be completed during the fall of 2020. A process and health economic evaluation will also be conducted.Ethics and dissemination This study was approved by the Regional Ethical Review Board in Gothenburg, Sweden. Results will be published in peer-reviewed scientific journals and presented at national and international scientific conferences. This project is part of a broader research programme conducted at the Gothenburg Centre for Person-Centred Care (GPCC), where extensive work is undertaken to disseminate knowledge on and implementation of PCC.Trial registration number NCT03404583.